Do improved property rights decrease violence against women in India? - Sofia Amaral (University of Essex, Institute for Social and Economic Research (ISER), 2017)
This paper uses the staggered implementation of a legal change in inheritance law in India to estimate the effect of women's improved access to inheritance on violence against women. I find that the aggregate rate of violence against women ( including female suicides) fell. This fall is due to changes in police-reported violence as well as in female mortality. The law did not change male mortality or other forms of non-gender based crime. Further, at the individual level I find that spouses eligible for inheritance are 17 percent less likely to be victims of domestic violence. These findings are explained by an improvement in marriage market negotiations and this led to women marrying partners that consume less alcohol.
Keywords: J12; J16; K42; O15; 330; Domestic Violence; Property Rights; Intra-household Distribution; Marriage Market